Technological Approaches for Novel Applications in Dairy Processing 2018
DOI: 10.5772/intechopen.74448
|View full text |Cite
|
Sign up to set email alerts
|

Potential of High Pressure Homogenization and Functional Strains for the Development of Novel Functional Dairy Foods

Abstract: Functional foods are one of the fastest increasing fields in the global food industry since they are positively perceived by the consumers as dietary strategies to reduce the incidence of illness in the humankind. Actually, the use of biotechnological strategies, based on the use of functional and specific strains and sustainable technologies, such as highpressure homogenization, can be a great chance to create innovation in the dairy field. Critical discussion on the actual scenario is the main topic of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Regarding the application of high homogenization pressures, results obtained in this study also differ from those obtained by other authors [15,16] who confirmed that it can change the structure of microorganisms and increase their hydrophobicity, thus facilitating their adhesion to the cells of the digestive tract. Quite possibly, as documented by Patrignani et al [42], response to HPH varies with the species and the characteristics of individual strains, as well as with the composition of the media containing the microorganism.…”
Section: Adhesion To Intestinal Epithelium After Fermentation As Affe...mentioning
confidence: 95%
“…Regarding the application of high homogenization pressures, results obtained in this study also differ from those obtained by other authors [15,16] who confirmed that it can change the structure of microorganisms and increase their hydrophobicity, thus facilitating their adhesion to the cells of the digestive tract. Quite possibly, as documented by Patrignani et al [42], response to HPH varies with the species and the characteristics of individual strains, as well as with the composition of the media containing the microorganism.…”
Section: Adhesion To Intestinal Epithelium After Fermentation As Affe...mentioning
confidence: 95%
“…Patrignani et al [99] reported that HPH could be used in fermented milk for several reasons: (1) to modulate the sensorial characteristics without harmful effects on shelf life and safety; (2) to improve the technological performances of probiotics; and (3) to change the functional features of lactic acid bacteria.…”
Section: High-pressure Homogenizationmentioning
confidence: 99%
“…An exhaustive discussion on the actual scenario concerning HPH treatment of functional dairy beverages was reported by Patrignani et al [99]. In particular, the authors mentioned a previous study on the effect of HPH on nonfat milk solids and milk fat on the technological performances of Lb.…”
Section: High-pressure Homogenizationmentioning
confidence: 99%